Implementation of Management Functions in Improving the Quality of Nursing Services in Hospitals - Lina Mardianti; Partono Siswosuharjo; M. Adila Rossa (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2024)
The quality of nursing care is a key indicator of hospital service quality, significantly influenced by the effectiveness of the implementation of nursing management functions. Management functions, including planning, organizing, directing, and controlling, play a crucial role in coordinating resources, directing nurse performance, and ensuring the delivery of nursing care according to established standards. This study aims to analyze the implementation of management functions in improving the quality of nursing care in hospitals. The study employed a quantitative design with a descriptive correlational approach. The sample consisted of 120 nurses working in the hospital's inpatient unit, selected using a purposive sampling technique. Data collection was conducted through a structured questionnaire that measured the implementation of management functions and the quality of nursing care. Data analysis included univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using multiple logistic regression. The results showed a significant relationship between the implementation of management functions and the quality of nursing care (p < 0.05). The multivariate analysis revealed that the directing function was the most dominant factor influencing the quality of nursing care compared to other management functions. Good implementation of management functions increases the chances of achieving quality, safe, and patient-oriented nursing care. The conclusion of this study confirms that strengthening the managerial competencies of ward heads and nursing leaders is a crucial strategy for sustainably improving the quality of nursing services in hospitals